Variable Immunogenic Potential of Wheat: Prospective for Selection of Innocuous Varieties for Celiac Disease Patients via in vitro Approach - Grover, Jasmine; Chhuneja, Parveen; Midha, Vandana; Ghia, Jean Eric; Deka, Dipak; Mukhopadhyay, Chandra Shekhar; Sood, Neena; Mahajan, Ramit; Singh, Arshdeep; Verma, Ramneek; Bansal, Ekta; Sood, Ajit (Frontiers in Immunology, 2019)
Celiac Disease is a multifactorial, autoimmune enteropathy activated by cereal proteins in genetically predisposed individuals carrying HLA DQ2/8 genes. A heterogenous gene combination of the cereal prolamins is documented in different wheat genotypes, which is suggestive of their variable immunogenic potential. In the current study, four wheat varieties (C591, C273, 9D and K78) identified via in silico analysis were analyzed for immunogenicity by measuring T-cell proliferation rate and levels of inflammatory cytokines (Interferon-γ and Tumor Necrosis Factor-α). Peripheral Blood Mononuclear Cells and biopsy derived T-cell lines isolated from four celiac disease patients in complete remission and two controls were stimulated and cultured in the presence of tissue transglutaminase activated pepsin-trypsin digest of total gliadin extract from test varieties. The immunogenicity was compared with PBW 621, one of the widely cultivated wheat varieties. Phytohaemagglutinin-p was taken as positive control, along with unstimulated cells as negative control. Rate of cell proliferation (0.318, 0.482; 0.369, 0.337), concentration of IFN- γ (107.4, 99.2; 117.9, 99.7pg/ml) and TNF- α (453.8, 514.2; 463.8, 514.2pg/ml) was minimum in cultures supplemented with wheat antigen from C273, when compared with other test varieties and unstimulated cells. Significant difference in toxicity levels among different wheat genotypes to stimulate celiac mucosal T-cells and PBMC’s was observed; where C273 manifested least immunogenic response amongst the test varieties analyzed.